2004
DOI: 10.1523/jneurosci.0671-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

A SingleIn VivoExposure to Cocaine Abolishes Endocannabinoid-Mediated Long-Term Depression in the Nucleus Accumbens

Abstract: In the nucleus accumbens (NAc), a key structure to the effects of all addictive drugs, presynaptic cannabinoid CB1 receptors (CB1Rs) and postsynaptic metabotropic glutamate 5 receptors (mGluR5s) are the principal effectors of endocannabinoid (eCB)-mediated retrograde long-term depression (LTD) (eCB-LTD) at the prefrontal cortex-NAc synapses. Both CB1R and mGluR5 are involved in cocaine-related behaviors; however, the impact of in vivo cocaine exposure on eCB-mediated retrograde synaptic plasticity remains unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
180
5
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(214 citation statements)
references
References 39 publications
23
180
5
2
Order By: Relevance
“…The changes in short-term plasticity observed in our study contrast several studies that did not observe significant changes in the paired-pulse ratio in mice that were either treated with or self-administered cocaine (Thomas et al, 2001;Fourgeaud et al, 2004;SchrammSapyta et al, 2006). This disparity most likely reflects differences between the pharmacological effects of cocaine and amphetamine.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…The changes in short-term plasticity observed in our study contrast several studies that did not observe significant changes in the paired-pulse ratio in mice that were either treated with or self-administered cocaine (Thomas et al, 2001;Fourgeaud et al, 2004;SchrammSapyta et al, 2006). This disparity most likely reflects differences between the pharmacological effects of cocaine and amphetamine.…”
Section: Discussioncontrasting
confidence: 97%
“…This is consistent with the finding that chronic cocaine administration produces an enhanced sensitivity to DA (Beurrier and Malenka, 2002). In addition, other investigators have found that presynaptic inhibition by endocannabinoids is unaffected by a single systemic injection of cocaine (Fourgeaud et al, 2004). Thus, presynaptic KOP receptor modulation of glutamate release in the NAc appears to be selectively lost following exposure to psychostimulants.…”
Section: Discussionsupporting
confidence: 89%
“…injection of either 0.9% saline or 30mg/kg cocaine, put back in their home cages and then sacrificed either 45 minutes or 24 hours later. These time points were chosen based on previous studies that showed glutamate levels peak at approximately 40 minutes following acute cocaine (Smith et al, 1995;Reid et al, 1997) and changes in mGluR5 expression 24 hours following a cocaine exposure (Fourgeaud et al, 2004).…”
Section: Experimental Procedures Animals and Cocaine Treatmentsmentioning
confidence: 99%
“…A single in vivo exposure to cocaine abolishes endocannabinoid mGluR5-mediated retrograde long-term depression (LTD) and decreases the surface expression of mGluR5 in the mouse accumbens (Fourgeaud et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation